2021
DOI: 10.1097/icl.0000000000000853
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Lubricating Effect of Hyaluronic Acid on Contact Lenses Using a Pendulum-Type Friction Tester Under Mimicking Physiological Conditions

Abstract: To evaluate the lubricating effect of hyaluronic acid (HA) on soft contact lenses (SCLs) measured using a pendulum-type friction tester. Methods: We measured the coefficient of friction (CoF) of narafilcon A, delefilcon A, and etafilcon A with polyvinylpyrrolidone (PVP), daily disposable SCL material, using a modified pendulum-type friction tester. Sample SCLs were set on an acrylic plastic half-ball and placed into the polyethylene terephthalate hemisphere cup filled with 0.4 mL of test lubricants that includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…Aligned with this, they also showed that concentrations of hyaluronic acid at 0.1%, 0.2%, 0.3%, 0.4%, and 0.5% increased the coefficient of friction of the same contact lenses, directly related to the concentration. 21 These contradictory results compared with this study would manifest the need to extrapolate these types of studies to clinical research, evaluating a wide range of contact lens materials, but also better methods to assess in vivo wettability. In addition, using a low concentration of hyaluronic acid (0.005%), Yamasaki et al 22 neither reported an effect on the in vitro wettability of another four different soft contact lenses.…”
Section: Discussionmentioning
confidence: 75%
“…Aligned with this, they also showed that concentrations of hyaluronic acid at 0.1%, 0.2%, 0.3%, 0.4%, and 0.5% increased the coefficient of friction of the same contact lenses, directly related to the concentration. 21 These contradictory results compared with this study would manifest the need to extrapolate these types of studies to clinical research, evaluating a wide range of contact lens materials, but also better methods to assess in vivo wettability. In addition, using a low concentration of hyaluronic acid (0.005%), Yamasaki et al 22 neither reported an effect on the in vitro wettability of another four different soft contact lenses.…”
Section: Discussionmentioning
confidence: 75%
“…Iwashita et al 15 also observed that 0.1% HA increased the contact angle (measured by the sessile drop technique) in the same contact lenses compared with the saline solution. 13 In contrast to the finding of the current study, the results of Iwashita et al 13,15 were not consistent with the idea that HA might produce a wetter surface by decreasing both the coefficient of friction and the contact angle. Iwashita et al 15 suggested that these contradictory results could be because of the effect of the viscosity of HA, which has a high molecular weight and behaves as a non-Newtonian fluid.…”
Section: Discussionmentioning
confidence: 84%
“…For example, Iwashita et al 15 reported that the coefficient of friction of four types of soft contact lenses increased with the concentration of HA (0.1%-0.5%). Iwashita et al 15 also observed that 0.1% HA increased the contact angle (measured by the sessile drop technique) in the same contact lenses compared with the saline solution. 13 In contrast to the finding of the current study, the results of Iwashita et al 13,15 were not consistent with the idea that HA might produce a wetter surface by decreasing both the coefficient of friction and the contact angle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dry eye syndrome is characterized by a loss of tear film homeostasis and ocular surface inflammation [72] . Due to high mucoadhesion, HW HA is efficient in precorneal water retention and protection of the ocular surface [73] . Meta-analyses have shown no clinical difference in the application of HA-based versus non-HA-based medications [74] but other medical studies, nevertheless, report that a HW HA lacrimal substitute has the potential to become an alternative to autologous serum eye drops in the treatment of dry eye syndrome [59] , [75] , [76] .…”
Section: Ha Applicationmentioning
confidence: 99%